2018
DOI: 10.1111/pbr.12563
|View full text |Cite
|
Sign up to set email alerts
|

A novel aphid resistance locus in cowpea identified by combining SSR and SNP markers

Abstract: The utility of combining simple sequence repeat (SSR) and single nucleotide polymorphism (SNP) marker genotyping was determined for genetically mapping a novel aphid (Aphis craccivora) resistance locus in cowpea breeding line SARC 1‐57‐2 and for introgressing the resistance into elite cultivars by marker‐assisted backcrossing (MABC). The locus was tagged with codominant SSR marker CP 171F/172R with a recombination fraction of 5.91% in an F2 population from ‘Apagbaala’ x SARC 1‐57‐2. A SNP‐genotyped biparental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Huynh et al (2015), using SNP markers, discovered two QTLs involved in aphid resistance of IT97K556‐6: a major QTL, QAc‐vu7, and a minor QTL, QAc‐vu1.1. However, monogenic aphid resistance in cowpeas has also been reported (Kusi et al, 2018; Omoigui et al, 2017). Boukar et al (2018) reported that the single dominant gene conferring aphid resistance in cowpeas and incorporated in several improved breeding lines and varieties has become ineffective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Huynh et al (2015), using SNP markers, discovered two QTLs involved in aphid resistance of IT97K556‐6: a major QTL, QAc‐vu7, and a minor QTL, QAc‐vu1.1. However, monogenic aphid resistance in cowpeas has also been reported (Kusi et al, 2018; Omoigui et al, 2017). Boukar et al (2018) reported that the single dominant gene conferring aphid resistance in cowpeas and incorporated in several improved breeding lines and varieties has become ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…Markers linked to aphid resistance have also been reported in other studies. For instance, Kusi et al (2018) and Omoigui et al (2017) working with cowpeas found two markers (CP171/172 and KAD61) linked to genes involved in aphid resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk of world cowpea production and consumption is in the savanna regions of West Africa [ 2 ], where Nigeria leads with an annual production of about 3.65 million metric tons [ 3 ]. Productivity of cowpea in this region and other parts of the world is hindered by numerous insect pests, cowpea aphids, A. craccivora Koch (Homoptera: Aphididae), being one of the most important pests, causing severe economic damage during the vegetative phase of the crop [ 4 , 5 , 6 , 7 ]. Like many sap-sucking insects, aphids cause damage in susceptible cowpea cultivars directly by altering plant metabolism and feeding on plant nutrients and indirectly by transmitting plant-pathogenic viruses, especially the aphid-borne cowpea mosaic viruses [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there has been increased effort in the search for sources of resistance to cowpea aphids and better understanding of the nature and mechanism of resistance. Several sources of resistance to aphids have been identified in different breeding programs [ 5 , 13 , 14 , 15 , 16 ]. Aphid resistance is a priority trait in the cowpea breeding program of the International Institute of Tropical Agriculture (IITA).…”
Section: Introductionmentioning
confidence: 99%